Lexicographic Voting - Jan Klingelhöfer (ZBW - Deutsche Zentralbibliothek für Wirtschaftswissenschaften, Leibniz-Informationszentrum Wirtschaft, 2011)
I reconsider the division of the literature into models with forward-looking voters and models with backward-looking voters by developing a model that incorporates motives from both literatures. As long as there is no uncertainty about preferences and parties can commit in advance to the ideological dimension of policy, but not to a maximal level of rent extraction, voters can constrain the latter to the same extent as in a purely backward-looking model. At the same time, the policy preferred by the median voter is implemented as in a standard forward-looking model of political competition. Voters achieve this outcome by following a simple lexicographic voting strategy. They cast their vote in favor of their favorite policy position whenever parties offer different platforms, but make their vote dependent on the incumbent parties' performance whenever they are indifferent. When uncertainty about the position of the median voter is introduced into the model, voters have to accept higher rent payments, but they still retain some control over rent extraction.
Keywords: D72; C72; D02; 330